Relationship between Organizational Culture and Workplace Bullying among Korean Nurses - Yuseon An, MS, RN; Jiyeon Kang, PhD, RN (Elsevier, 2016)
Purpose: To identify the relationship between organizational culture and experience of workplace bullying among Korean nurses. Methods: Participants were 298 hospital nurses in Busan, South Korea. We assessed nursing organizational culture and workplace bullying among nurses using structured questionnaires from July 1 through August 15, 2014. Results: Most participants considered their organizational culture as hierarchy-oriented (45.5%), followed by relation-oriented (36.0%), innovation-oriented (10.4%), and task-oriented (8.1%). According to the operational bullying criteria, the prevalence of workplace bullying was 15.8%. A multivariate logistic regression analysis revealed that the odds of being a victim of bullying were 2.58 times as high among nurses in a hierarchy-oriented culture as among nurses in a relation-oriented culture [95% confidence interval (1.12, 5.94)]. Conclusions: The results suggest that the types of nursing organizational culture are related to workplace bullying in Korean nurses. Further research is needed to develop interventions that can foster relation-oriented cultures to prevent workplace bullying in nurses.